On the formation mechanism of impurity-helium solids: evidence for extensive clustering - Popov, E.A.; Eloranta, J.; Ahokas, J.; Kunttu, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Optical emission studies on a discharged nitrogen-helium gas jet injected into superfluid helium near 1.5 K are described. The analysis of atomic (a-group) and molecular Vegard-Kaplan transitions clearly indicates that the emitting species are embedded in the nitrogen clusters. The formation of the clusters is most efficient in the crater formed on the liquid surface. The model calculations based on the classical bubble model and density functional theory suggest that under the experimental conditions only clusters consisting of more than 1000 molecules have a kinetic energy sufficient for the stable cavity formation inside liquid helium. The results obtained suggest that the formation of impurity-helium solids is a consequence of extensive clustering in the gas jet.